2016
DOI: 10.1177/0886260516664317
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Dispositional Mindfulness, Distress Tolerance, and Women’s Dating Violence Perpetration: A Path Analysis

Abstract: Scant research examined mechanisms underlying the relationship between dispositional mindfulness and dating violence (DV) perpetration. Using a cross-sectional design with 203 college women, we examined whether distress tolerance mediated the relationship between dispositional mindfulness and DV perpetration (i.e., psychological aggression and physical assault). Path analyses results revealed indirect effects of mindfulness facets nonjudging of inner experiences and nonreactivity to inner experiences on both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
2
14
2
Order By: Relevance
“…That is, it seems likely that in reacting to emotional states, particularly negative ones that precede or coincide with relationship aggression, individuals may engage in destructive behaviors, including aggression. While not directly predicted by our hypotheses, it is not inconsistent with other recent research in IPV suggesting a relationship between physical IPV perpetration and nonjudging (Brem et al, 2019). These data also suggested that nonjudging was related to lower levels of both physical and psychological perpetration through distress tolerance, which has been linked to IPV (Brem et al, 2019; Shorey et al, 2017).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…That is, it seems likely that in reacting to emotional states, particularly negative ones that precede or coincide with relationship aggression, individuals may engage in destructive behaviors, including aggression. While not directly predicted by our hypotheses, it is not inconsistent with other recent research in IPV suggesting a relationship between physical IPV perpetration and nonjudging (Brem et al, 2019). These data also suggested that nonjudging was related to lower levels of both physical and psychological perpetration through distress tolerance, which has been linked to IPV (Brem et al, 2019; Shorey et al, 2017).…”
Section: Discussioncontrasting
confidence: 90%
“…While not directly predicted by our hypotheses, it is not inconsistent with other recent research in IPV suggesting a relationship between physical IPV perpetration and nonjudging (Brem et al, 2019). These data also suggested that nonjudging was related to lower levels of both physical and psychological perpetration through distress tolerance, which has been linked to IPV (Brem et al, 2019; Shorey et al, 2017).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Two factors worth examining in this regard are emotion dysregulation and distress intolerance, both of which have been found to be associated with PTSD (e.g., Marshall-Berenz, Vujanovic, Bonn-Miller, Bernstein, & Zvolensky, 2010; Weiss, Tull, Anestis, et al, 2013) and aggressive behaviors (e.g., Brem et al, in press; Gratz, Paulson, Jakupcak, & Tull, 2009). Of note, whereas negative urgency has some overlap with emotion dysregulation and distress intolerance, there are important distinctions between these constructs.…”
Section: Discussionmentioning
confidence: 99%